Carbon nanotube-based anti-static ABS composite material and preparation method thereof

By using carbon nanotubes and MoS2 quantum dots in ABS composites, the electrostatic, heat resistance and impact resistance of ABS composites are solved, and excellent conductivity and mechanical properties are achieved Performance, reduces costs.

CN119307065AActive Publication Date: 2025-01-14JIANGXI PLASTIC HIGH-TECH MATERIALS CO LTD

Patent Information

Application Number
CN202411865840.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-01-14
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

ABS composites are prone to static electricity during use, which limits their application in electronic products and automobile manufacturing fields. At the same time, it is necessary to improve their heat resistance and impact resistance. Traditional antistatic materials are costly and have limited effects.

Method used

Using anti-static ABS composite materials based on carbon nanotubes, by preparing composite conductive fillers and modified heat-resistant agents, carbon nanotubes and MoS2 quantum dots jointly exert the conductive network, improve conductivity and mechanical properties, and modify heat-resistant The agent improves heat resistance.

Benefits of technology

The excellent antistatic properties, mechanical properties and impact strength of composite materials are achieved, while reducing production costs, improving heat resistance, reducing surface resistivity, and significantly improving impact strength and heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of ABS (Acrylonitrile Butadiene Styrene) composite materials, and discloses an anti-static ABS composite material based on a carbon nanotube and a preparation method of the anti-static ABS composite material. The anti-static ABS composite material prepared by the invention is prepared from the following raw materials in parts by weight: 70 to 90 parts of ABS resin, 8 to 15 parts of polycarbonate resin, 5 to 12 parts of composite conductive filler, 1 to 3 parts of lubricant, 5 to 10 parts of modified heat-resistant agent and 0.2 to 0.4 part of antioxidant, aBS resin is used as matrix resin, and polycarbonate resin is added to improve the comprehensive performance of the composite material; a carbon nano tube is used as a substrate, a composite conductive filler is prepared through modification, the conductivity of the substrate is improved, and then the antistatic performance, the mechanical performance and the impact strength of the substrate are improved; and the heat resistance of the matrix is improved by adding the modified heat-resistant agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ABS composite materials, and in particular to an anti-static ABS composite material based on carbon nanotubes and a preparation method thereof. Background Art

[0002] ABS resin is made of three chemical substances, butadiene, acrylonitrile and styrene, through polymerization and blending processes. Therefore, ABS resin has the chemical resistance and weather resistance provided by acrylonitrile, the high impact and high rigidity provided by butadiene, and the high fluidity and easy processing of products provided by styrene. ABS resin can be widely used in home appliances, automobile transportation, toy products, daily necessities and other fields, and is currently one of the world's top five general-purpose plastics.

[0003] However, ABS composite materials have good insulation properties, which makes its products prone to static electricity during use, which limits its application in electronic products, automobile manufacturing and other fields. Traditional antistatic ABS composite materials mainly use permanent antistatic agents (expensive) or high content of conductive carbon black, carbon nanotubes, etc. to improve the antistatic properties of composite materials, but single use will result in high production costs. In addition, considering that ABS composite materials may also need to be used in high temperature environments, their heat resistance needs to be improved. Therefore, in response to the above problems, researchers need to develop an antistatic ABS composite material with excellent antistatic properties, heat resistance, impact resistance and mechanical properties. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides an anti-static ABS composite material based on carbon nanotubes and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A carbon nanotube-based anti-static ABS composite material comprises the following raw materials in parts by weight: 70-90 parts of ABS resin, 8-15 parts of polycarbonate resin, 5-12 parts of composite conductive filler, 1-3 parts of lubricant, 5-10 parts of modified heat-resistant agent, and 0.2-0.4 parts of antioxidant; Further, the lubricant is one of calcium stearate, polyethylene wax or zinc stearate; Further, the antioxidant is one of antioxidant 1010, antioxidant 1098 and antioxidant 1076; The composite conductive filler is prepared by the following steps: Step A1, ultrasonically treating carbon nanotubes (CNTs) in deionized water for 30 minutes, then adding mixed acid, refluxing and stirring at 100° C. for 3-4 hours, centrifuging, washing to neutrality, and drying to obtain pre-treated carbon nanotubes; Step A2, mix ammonium molybdate tetrahydrate in deionized water, adjust the pH to 6-6.5, add reduced glutathione aqueous solution and stir for 10-20 minutes, then add pretreated carbon nanotubes and stir evenly, then transfer to an autoclave, react at 160-200°C for 24 hours, centrifuge, wash and dry to obtain MoS2@CNTs (MoS2 quantum dot-loaded carbon nanotubes); Step A3, disperse MoS2@CNTs evenly in 1,4-dioxane, add γ-mercaptopropyltriethoxysilane, heat to 80-90°C, stir to react for 4-6h, filter, wash, and collect thiolated MoS2@CNTs; then stir nonylphenol polyoxyethylene ether evenly in deionized water, add thiolated MoS2@CNTs solution and 2-acrylamide-2-methylpropanesulfonic acid under nitrogen, and add 0.03 mol / L triethylamine aqueous solution, adjust the system pH to 9-10, heat to 75-85°C, stir to react for 6-8h, filter, wash, and dry to obtain a composite conductive filler; Furthermore, in step A1, the amount ratio of carbon nanotubes, deionized water and mixed acid is 0.3-0.5 g: 10 mL: 40 mL, and the mixed acid is prepared by mixing 98 wt % concentrated sulfuric acid and 68 wt % concentrated nitric acid in a volume ratio of 3:1; Furthermore, in step A2, the ratio of ammonium molybdate tetrahydrate, deionized water, reduced glutathione aqueous solution and pre-treated carbon nanotubes is 0.5-1.5 g: 80 mL: 20 mL: 1-3 g, and the reduced glutathione aqueous solution is prepared by mixing and stirring reduced glutathione and deionized water in a ratio of 2.5-7.5 g: 20 mL; Further, in step A3, the amount ratio of MoS2@CNTs, 1,4-dioxane and γ-mercaptopropyltriethoxysilane in the thiolation MoS2@CNTs is 0.5-2 g: 50 mL: 0.3-1.5 g; Furthermore, in step A3, the dosage ratio of nonylphenol polyoxyethylene ether, deionized water, thiolated MoS2@CNTs solution, 2-acrylamide-2-methylpropanesulfonic acid and triethylamine aqueous solution in the composite conductive filler is 2-3g:100mL:50mL:0.5-2g:10mL, and the thiolated MoS2@CNTs solution is prepared by mixing and stirring thiolated MoS2@CNTs and deionized water in a dosage ratio of 0.5-1.5g:50mL.

[0006] The modified heat-resistant agent is prepared by the following steps: Step B1, 2,5-diaminophenol hydrochloride, 4-vinylbenzoic acid and polyphosphoric acid are mixed and stirred, and heated to 100-110° C., reacted for 30 minutes, and then heated to 200° C. for reaction for 2-3 hours, filtered, washed, and collected the product, and then the product was allowed to stand in a 10wt% sodium carbonate aqueous solution for 12 hours, filtered, washed, and dried to obtain a functional monomer; Step B2, maleic anhydride is mixed evenly in N,N-dimethylformamide, recorded as solution 1; melamine is mixed evenly in N,N-dimethylformamide, recorded as solution 2; solution 2 is slowly added to solution 1 to react for 1.5-2.5h, anhydrous sodium acetate and hydroquinone are added and stirred evenly, acetic anhydride is added, and the temperature is raised to 45-55°C to react for 2h, cooled, filtered, washed and dried to obtain a maleic anhydride grafted product; Step B3, the functional monomer and the maleic anhydride grafted product are mixed and stirred in cyclohexanone, and then transferred to an oil bath pot and heated at 70-80°C for reaction for 30-50 minutes, and then nitrogen is introduced, benzoyl peroxide is added, and the temperature is raised to 100°C for reaction for 3.5-4.5 hours. After cooling, it is precipitated in petroleum ether and acetone in turn, filtered and dried to obtain a modified heat-resistant agent; Further, in step B1, the usage ratio of 2,5-p-diaminophenol hydrochloride, 4-vinylbenzoic acid, polyphosphoric acid and sodium carbonate aqueous solution is 0.01-0.03 mol: 0.01-0.03 mol: 8-24 g: 50 mL; Further, in step B2, the dosage ratio of solution 1, solution 2, anhydrous sodium acetate, hydroquinone and acetic anhydride is 40 mL: 40 mL: 1-2 g: 0.8-1.6 g: 4-8 mL, the dosage ratio of maleic anhydride and N, N-dimethylformamide in solution 1 is 0.05-0.1 mol: 40 mL, and the dosage ratio of melamine and N, N-dimethylformamide in solution 2 is 0.05-0.1 mol: 40 mL; Furthermore, in step B3, the usage ratio of the functional monomer, the maleic anhydride graft, the cyclohexanone, the benzoyl peroxide, the petroleum ether and the acetone is 5-8 g: 3-6 g: 30 mL: 0.4-0.6 g: 50 mL: 50 mL.

[0007] A method for preparing an anti-static ABS composite material based on carbon nanotubes comprises the following steps: The raw materials are weighed by weight, and ABS resin, polycarbonate resin, composite conductive filler, lubricant, modified heat-resistant agent and antioxidant are mixed and stirred evenly, and then put into a twin-screw extruder, and melted, extruded and granulated to obtain an anti-static ABS composite material based on carbon nanotubes.

[0008] Beneficial effects of the present invention: The anti-static ABS composite material prepared by the present invention uses ABS resin as a matrix resin, and polycarbonate resin is added to improve the comprehensive performance of the composite material; carbon nanotubes are used as a substrate, and a composite conductive filler is prepared by modification to improve the conductivity of the matrix, thereby improving the antistatic performance, mechanical properties and impact strength of the matrix; the addition of a modified heat-resistant agent improves the heat resistance of the matrix.

[0009] The composite conductive filler uses mixed acid to pre-treat carbon nanotubes to improve the dispersibility of carbon nanotubes; then, ammonium molybdate tetrahydrate and reduced glutathione are used as raw materials to load MoS2 quantum dots on the pre-treated carbon nanotubes to obtain MoS2@CNTs; then, a silane coupling agent is used to modify the surface of MoS2@CNTs to obtain thiol-modified MoS2@CNTs, and finally, the thiol groups on the surface of MoS2@CNTs react with the double bonds in 2-acrylamide-2-methylpropanesulfonic acid to obtain a composite conductive filler. The composite conductive filler uses the synergistic effect between carbon nanotubes and MoS2 quantum dots to form a conductive network in the matrix, so that current can flow therein, thereby realizing the conductive function, reducing the surface resistivity of the matrix, and improving the conductivity of the matrix; in addition, the surface of the composite antistatic agent is also grafted with a sulfonic acid group with excellent hydrophilicity, which can adsorb trace moisture in the environment on the surface of the material to form a layer of water film, which has a conductive effect, can help release the surface charge of the material, reduce static electricity accumulation, and further improve the antistatic effect of the matrix. In addition, the carbon nanotubes in the composite conductive filler can also improve the mechanical properties and impact strength of the matrix.

[0010] In the modified heat-resistant agent, 2,5-p-diaminophenol hydrochloride and 4-vinylbenzoic acid are first reacted to generate a functional monomer containing a benzoxazole structure and a terminal double bond structure; then maleic anhydride and melamine are reacted to obtain a maleic anhydride graft containing an imide structure; finally, under the action of an initiator, the functional monomer and the maleic anhydride graft are subjected to a free radical copolymerization reaction to synthesize the modified heat-resistant agent. The modified heat-resistant agent introduces an imide group, a benzoxazole structure, and a triazine structure with excellent heat resistance, and the three act synergistically to improve the heat resistance of the matrix; in addition, the active group (amino group) in the modified heat-resistant agent can also chemically bond with the maleic anhydride structure contained in the ABS resin when it is melted, reducing the degradation of heat resistance due to migration, precipitation, and other problems. DETAILED DESCRIPTION

[0011] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0012] Example 1: The composite conductive filler is prepared by the following steps: Step A1, ultrasonically treat 0.3 g of carbon nanotubes in 10 mL of deionized water for 30 min, then add 40 mL of mixed acid (mixed by 98 wt % concentrated sulfuric acid and 68 wt % concentrated nitric acid in a volume ratio of 3:1), reflux and stir at 100° C. for 3 h, centrifuge, wash to neutrality, and dry to obtain pre-treated carbon nanotubes; Step A2, 0.5 g of ammonium molybdate tetrahydrate was mixed in 80 mL of deionized water, and the pH was adjusted to 6, 20 mL of reduced glutathione aqueous solution was added and stirred for 10 min, and then 1 g of pretreated carbon nanotubes was added and stirred evenly, and then transferred to an autoclave, reacted at 160 ° C for 24 h, centrifuged, washed, and dried to obtain MoS2@CNTs, and the reduced glutathione aqueous solution was prepared by mixing and stirring reduced glutathione and deionized water in a dosage ratio of 2.5 g: 20 mL; Step A3, 0.5g MoS2@CNTs was evenly dispersed in 50mL 1,4-dioxane, and then 0.3g γ-mercaptopropyltriethoxysilane was added, the temperature was raised to 80°C, stirred for reaction for 4h, filtered, washed, and the thiolated MoS2@CNTs were collected; then 2g nonylphenol polyoxyethylene ether was evenly stirred in 100mL deionized water, and then 50mL of thiolated MoS2@CNTs solution and 0.5g 2-acrylamide-2-methylpropanesulfonic acid were added under nitrogen conditions, and 10mL, 0.03mol / L triethylamine aqueous solution was added at the same time, and the pH of the system was adjusted to 9, the temperature was raised to 75°C, stirred for reaction for 6h, filtered, washed, and dried to obtain a composite conductive filler. The thiolated MoS2@CNTs solution was prepared by mixing and stirring the thiolated MoS2@CNTs and deionized water in a dosage ratio of 0.5g:50mL.

[0013] The modified heat-resistant agent is prepared by the following steps: Step B1, 0.01 mol of 2,5-diaminophenol hydrochloride, 0.01 mol of 4-vinylbenzoic acid and 8 g of polyphosphoric acid were mixed and stirred, and heated to 100° C., reacted for 30 min, and then heated to 200° C. for 2 h, filtered, washed, and collected the product, and then the product was allowed to stand in 50 mL, 10 wt% sodium carbonate aqueous solution for 12 h, filtered, washed, and dried to obtain a functional monomer; Step B2, 0.05 mol of maleic anhydride was mixed evenly in 40 mL of N, N-dimethylformamide, recorded as solution 1; 0.05 mol of melamine was mixed evenly in 40 mL of N, N-dimethylformamide, recorded as solution 2; 40 mL of solution 2 was slowly added to 40 mL of solution 1 to react for 1.5 h, and then 1 g of anhydrous sodium acetate and 0.8 g of hydroquinone were added and stirred evenly, and then 4 mL of acetic anhydride was added, and the temperature was raised to 45° C. to react for 2 h, cooled, filtered, washed, and dried to obtain a maleic anhydride grafted product; Step B3, 5g of the functional monomer and 3g of the maleic anhydride grafted product were mixed and stirred evenly in 30mL of cyclohexanone, then transferred to an oil bath and heated at 70°C for 30min, then nitrogen was introduced, 0.4g of benzoyl peroxide was added, and the temperature was raised to 100°C for 3.5h. After cooling, it was precipitated in 50mL of petroleum ether and 50mL of acetone, filtered and dried to obtain a modified heat-resistant agent.

[0014] Example 2: The composite conductive filler is prepared by the following steps: Step A1, ultrasonically treat 0.4 g of carbon nanotubes in 10 mL of deionized water for 30 min, then add 40 mL of mixed acid (mixed by 98 wt % concentrated sulfuric acid and 68 wt % concentrated nitric acid in a volume ratio of 3:1), reflux and stir at 100° C. for 3.5 h, centrifuge, wash to neutrality, and dry to obtain pre-treated carbon nanotubes; Step A2, 1g of ammonium molybdate tetrahydrate was mixed in 80mL of deionized water, and the pH was adjusted to 6.3, 20mL of reduced glutathione aqueous solution was added and stirred for 15min, and then 1-3g of pretreated carbon nanotubes were added and stirred evenly, and then transferred to an autoclave, reacted at 180°C for 24h, centrifuged, washed, and dried to obtain MoS2@CNTs, and the reduced glutathione aqueous solution was prepared by mixing and stirring reduced glutathione and deionized water in a dosage ratio of 5g:20mL; Step A3, 1g MoS2@CNTs was evenly dispersed in 50mL 1,4-dioxane, and then 0.9g γ-mercaptopropyltriethoxysilane was added, the temperature was raised to 85°C, stirred for reaction for 5h, filtered, washed, and the thiolated MoS2@CNTs were collected; then 2.5g nonylphenol polyoxyethylene ether was evenly stirred in 100mL deionized water, and then 50mL of thiolated MoS2@CNTs solution and 1g 2-acrylamide-2-methylpropanesulfonic acid were added under nitrogen conditions, and 10mL, 0.03mol / L triethylamine aqueous solution was added at the same time, the pH of the system was adjusted to 9.5, the temperature was raised to 80°C, stirred for reaction for 7h, filtered, washed, and dried to obtain a composite conductive filler. The thiolated MoS2@CNTs solution was prepared by mixing and stirring the thiolated MoS2@CNTs and deionized water in a dosage ratio of 1g:50mL.

[0015] The modified heat-resistant agent is prepared by the following steps: Step B1, 0.02 mol of 2,5-diaminophenol hydrochloride, 0.02 mol of 4-vinylbenzoic acid and 16 g of polyphosphoric acid were mixed and stirred, and heated to 105° C., reacted for 30 min, and then heated to 200° C. for 2.5 h, filtered, washed, and collected the product, and then the product was allowed to stand in 50 mL, 10 wt% sodium carbonate aqueous solution for 12 h, filtered, washed, and dried to obtain a functional monomer; Step B2, 0.075 mol of maleic anhydride was mixed evenly in 40 mL of N, N-dimethylformamide, recorded as solution 1; 0.075 mol of melamine was mixed evenly in 40 mL of N, N-dimethylformamide, recorded as solution 2; 40 mL of solution 2 was slowly added to 40 mL of solution 1 to react for 2 h, and then 1.5 g of anhydrous sodium acetate and 1.2 g of hydroquinone were added and stirred evenly, and then 6 mL of acetic anhydride was added, and the temperature was raised to 50° C. to react for 2 h, cooled, filtered, washed, and dried to obtain a maleic anhydride grafted product; Step B3, 6.5g of functional monomer and 4.5g of maleic anhydride grafted product were mixed and stirred evenly in 30mL of cyclohexanone, then transferred to an oil bath and heated at 75°C for 40min, then nitrogen was introduced, 0.5g of benzoyl peroxide was added, and the temperature was raised to 100°C for 4h. After cooling, it was precipitated in 50mL of petroleum ether and 50mL of acetone, filtered and dried to obtain a modified heat-resistant agent.

[0016] Example 3: The composite conductive filler is prepared by the following steps: Step A1, ultrasonically treat 0.5 g of carbon nanotubes in 10 mL of deionized water for 30 min, then add 40 mL of mixed acid (mixed by 98 wt % concentrated sulfuric acid and 68 wt % concentrated nitric acid in a volume ratio of 3:1), reflux and stir at 100° C. for 4 h, centrifuge, wash to neutrality, and dry to obtain pre-treated carbon nanotubes; Step A2, 1.5g of ammonium molybdate tetrahydrate was mixed in 80mL of deionized water, and the pH was adjusted to 6.5, 20mL of reduced glutathione aqueous solution was added and stirred for 20min, and then 1-3g of pretreated carbon nanotubes were added and stirred evenly, and then transferred to an autoclave, reacted at 200°C for 24h, centrifuged, washed, and dried to obtain MoS2@CNTs, wherein the reduced glutathione aqueous solution was prepared by mixing and stirring reduced glutathione and deionized water in a dosage ratio of 7.5g:20mL; Step A3, 2g MoS2@CNTs are evenly dispersed in 50mL 1,4-dioxane, and then 1.5g γ-mercaptopropyltriethoxysilane is added, the temperature is raised to 90°C, stirred for reaction for 6h, filtered, washed, and the thiolated MoS2@CNTs are collected; then 3g nonylphenol polyoxyethylene ether is evenly stirred in 100mL deionized water, and then under nitrogen conditions, 50mL of thiolated MoS2@CNTs solution and 2g 2-acrylamide-2-methylpropanesulfonic acid are added, and 10mL, 0.03mol / L triethylamine aqueous solution is added at the same time, and then the pH of the system is adjusted to 10, the temperature is raised to 85°C, stirred for reaction for 8h, filtered, washed, and dried to obtain a composite conductive filler. The thiolated MoS2@CNTs solution is prepared by mixing and stirring the thiolated MoS2@CNTs and deionized water in a dosage ratio of 1.5g:50mL.

[0017] The modified heat-resistant agent is prepared by the following steps: Step B1, 0.03 mol of 2,5-diaminophenol hydrochloride, 0.03 mol of 4-vinylbenzoic acid and 24 g of polyphosphoric acid were mixed and stirred, and heated to 110° C. for reaction for 30 min, and then heated to 200° C. for reaction for 3 h, filtered, washed, and collected the product, and then the product was allowed to stand in 50 mL, 10 wt% sodium carbonate aqueous solution for 12 h, filtered, washed, and dried to obtain a functional monomer; Step B2, 0.1 mol of maleic anhydride was mixed evenly in 40 mL of N, N-dimethylformamide, recorded as solution 1; 0.1 mol of melamine was mixed evenly in 40 mL of N, N-dimethylformamide, recorded as solution 2; 40 mL of solution 2 was slowly added to 40 mL of solution 1 to react for 2.5 h, and then 2 g of anhydrous sodium acetate and 1.6 g of hydroquinone were added and stirred evenly, and then 8 mL of acetic anhydride was added, and the temperature was raised to 55 ° C. to react for 2 h, cooled, filtered, washed, and dried to obtain a maleic anhydride grafted product; Step B3, 8g of the functional monomer and 6g of the maleic anhydride grafted product were mixed and stirred evenly in 30mL of cyclohexanone, then transferred to an oil bath and heated at 80°C for 30-50min, then nitrogen was introduced, 0.6g of benzoyl peroxide was added, and the temperature was raised to 100°C for 4.5h. After cooling, it was precipitated in 50mL of petroleum ether and 50mL of acetone, filtered and dried to obtain a modified heat-resistant agent.

[0018] Embodiment 4: A method for preparing an anti-static ABS composite material based on carbon nanotubes comprises the following steps: ABS resin 70 parts, polycarbonate resin 8 parts, composite conductive filler prepared in Example 1 5 parts, calcium stearate 1 part, modified heat-resistant agent prepared in Example 1 5 parts, antioxidant 1010 0.2 parts; The raw materials were weighed by weight, and ABS resin, polycarbonate resin, the composite conductive filler prepared in Example 1, calcium stearate, the modified heat-resistant agent prepared in Example 1 and antioxidant 1010 were mixed and stirred evenly, and then put into a twin-screw extruder, and melted, extruded and granulated to obtain an anti-static ABS composite material based on carbon nanotubes.

[0019] Embodiment 5: A method for preparing an anti-static ABS composite material based on carbon nanotubes comprises the following steps: 80 parts of ABS resin, 12 parts of polycarbonate resin, 9 parts of the composite conductive filler prepared in Example 2, 2 parts of polyethylene wax, 8 parts of the modified heat-resistant agent prepared in Example 2, and 0.3 parts of antioxidant 1098; The raw materials are weighed by weight, and ABS resin, polycarbonate resin, the composite conductive filler prepared in Example 2, polyethylene wax, the modified heat-resistant agent prepared in Example 2 and antioxidant 1098 are mixed and stirred evenly, and put into a twin-screw extruder. After melting, extrusion and granulation, an anti-static ABS composite material based on carbon nanotubes is obtained.

[0020] Example 6: A method for preparing an anti-static ABS composite material based on carbon nanotubes comprises the following steps: 90 parts of ABS resin, 15 parts of polycarbonate resin, 12 parts of the composite conductive filler prepared in Example 3, 3 parts of zinc stearate, 10 parts of the modified heat-resistant agent prepared in Example 3, and 0.4 parts of antioxidant 1076; The raw materials are weighed by weight, and ABS resin, polycarbonate resin, the composite conductive filler prepared in Example 3, zinc stearate, the modified heat-resistant agent prepared in Example 3 and antioxidant 1076 are mixed and stirred evenly, and put into a twin-screw extruder. After melting, extrusion and granulation, an anti-static ABS composite material based on carbon nanotubes is obtained.

[0021] Comparative Example 1: This comparative example is an anti-static ABS composite material, which differs from Example 6 in that carbon black is used instead of the composite conductive filler prepared in Example 3, and the rest are the same.

[0022] Comparative Example 2: This comparative example is an anti-static ABS composite material. The difference from Example 6 is that α-methylstyrene is used instead of the modified heat-resistant agent prepared in Example 3, and the rest is the same.

[0023] The anti-static ABS composite materials prepared in Examples 4-6 and Comparative Examples 1-2 were injection molded into standard-sized specimens by an injection molding machine for performance testing; Surface resistivity test: Test surface resistivity according to IEC60093 standard; Heat resistance test: Use VicoMetco WKT-VST300D to measure the heat deformation temperature, test conditions: 50℃ / h (5±0.5℃ / 6min); Tensile strength test: Use a universal tensile testing machine to test the tensile properties of a 20cm×2cm×0.4cm strip sample; Impact strength test: Tested according to DIN ISO 179-1, with a pendulum energy of 4J; The test results are shown in Table 1:

[0024] It can be seen from Table 1 that after the surface resistivity, heat resistance, tensile strength and impact strength tests, the surface resistivity of the anti-static ABS composite material prepared by the present invention is (1.9×10 6 -4.6×10 6 )Ω, softening point is (126.3-138.1)℃, tensile strength is (45-48)MPa, impact strength is (17.6-18.2)kJ / m 2 , indicating that the composite material has excellent antistatic properties, heat resistance, mechanical strength and impact resistance.

[0025] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. An anti-static ABS composite material based on carbon nanotubes, characterized in that: The invention comprises the following raw materials in parts by weight: 70-90 parts of ABS resin, 8-15 parts of polycarbonate resin, 5-12 parts of composite conductive filler, 1-3 parts of lubricant, 5-10 parts of modified heat-resistant agent, and 0.2-0.4 parts of antioxidant; The composite conductive filler is prepared by the following steps: Step A1, ultrasonically treat the carbon nanotubes in deionized water for 30 minutes, then add a mixed acid, reflux and stir at 100° C. for 3-4 hours, centrifuge, wash until neutral, and dry to obtain pre-treated carbon nanotubes; Step A2, mix ammonium molybdate tetrahydrate in deionized water, adjust the pH to 6-6.5, add reduced glutathione aqueous solution and stir for 10-20 minutes, then add pretreated carbon nanotubes and stir evenly, then transfer to an autoclave, react at 160-200°C for 24 hours, centrifuge, wash and dry to obtain MoS2@CNTs; Step A3, dispersing MoS2@CNTs evenly in 1,4-dioxane, adding γ-mercaptopropyltriethoxysilane, heating to 80-90°C, stirring and reacting for 4-6h, filtering, washing, and collecting the thiolated MoS2@CNTs; Then, nonylphenol polyoxyethylene ether is stirred evenly in deionized water, and then, thiolated MoS2@CNTs solution and 2-acrylamide-2-methylpropane sulfonic acid are added under nitrogen conditions, and 0.03 mol / L triethylamine aqueous solution is added at the same time. Then, the pH of the system is adjusted to 9-10, the temperature is raised to 75-85°C, the reaction is stirred for 6-8h, and the composite conductive filler is obtained by filtering, washing and drying.

2. The anti-static ABS composite material based on carbon nanotubes according to claim 1, characterized in that: In step A1, the amount ratio of carbon nanotubes, deionized water and mixed acid is 0.3-0.5 g: 10 mL: 40 mL, and the mixed acid is prepared by mixing 98 wt % concentrated sulfuric acid and 68 wt % concentrated nitric acid in a volume ratio of 3:

1.

3. The anti-static ABS composite material based on carbon nanotubes according to claim 1, characterized in that: In step A2, the amount ratio of ammonium molybdate tetrahydrate, deionized water, reduced glutathione aqueous solution and pre-treated carbon nanotubes is 0.5-1.5 g: 80 mL: 20 mL: 1-3 g, and the reduced glutathione aqueous solution is prepared by mixing and stirring reduced glutathione and deionized water in an amount ratio of 2.5-7.5 g: 20 mL.

4. The anti-static ABS composite material based on carbon nanotubes according to claim 1, characterized in that: In step A3, the amount ratio of MoS2@CNTs, 1,4-dioxane and γ-mercaptopropyltriethoxysilane in the thiolated MoS2@CNTs is 0.5-2g:50mL:0.3-1.5g, and the amount ratio of nonylphenol polyoxyethylene ether, deionized water, thiolated MoS2@CNTs solution, 2-acrylamide-2-methylpropanesulfonic acid and triethylamine aqueous solution in the composite conductive filler is 2-3g:100mL:50mL:0.5-2g:10mL. The thiolated MoS2@CNTs solution is prepared by mixing and stirring the thiolated MoS2@CNTs and deionized water in a dosage ratio of 0.5-1.5g:50mL.

5. The anti-static ABS composite material based on carbon nanotubes according to claim 1, characterized in that: The modified heat-resistant agent is prepared by the following steps: Step B1, 2,5-diaminophenol hydrochloride, 4-vinylbenzoic acid and polyphosphoric acid are mixed and stirred, and heated to 100-110° C., reacted for 30 minutes, and then heated to 200° C. for reaction for 2-3 hours, filtered, washed, and collected the product, and then the product was allowed to stand in a 10wt% sodium carbonate aqueous solution for 12 hours, filtered, washed, and dried to obtain a functional monomer; Step B2, maleic anhydride is mixed evenly in N,N-dimethylformamide, recorded as solution 1; melamine is mixed evenly in N,N-dimethylformamide, recorded as solution 2; solution 2 is slowly added to solution 1 to react for 1.5-2.5h, anhydrous sodium acetate and hydroquinone are added and stirred evenly, acetic anhydride is added, and the temperature is raised to 45-55°C to react for 2h, cooled, filtered, washed and dried to obtain a maleic anhydride grafted product; Step B3, the functional monomer and the maleic anhydride grafted product are mixed and stirred evenly in cyclohexanone, then transferred to an oil bath pot and heated at 70-80°C for reaction for 30-50min, then nitrogen is introduced, benzoyl peroxide is added, and the temperature is raised to 100°C for reaction for 3.5-4.5h. After cooling, it is precipitated in petroleum ether and acetone in turn, filtered and dried to obtain a modified heat-resistant agent.

6. The anti-static ABS composite material based on carbon nanotubes according to claim 5, characterized in that: In step B1, the usage ratio of 2,5-p-diaminophenol hydrochloride, 4-vinylbenzoic acid, polyphosphoric acid and sodium carbonate aqueous solution is 0.01-0.03 mol: 0.01-0.03 mol: 8-24 g: 50 mL.

7. The anti-static ABS composite material based on carbon nanotubes according to claim 5, characterized in that: In step B2, the dosage ratio of solution 1, solution 2, anhydrous sodium acetate, hydroquinone and acetic anhydride is 40 mL: 40 mL: 1-2 g: 0.8-1.6 g: 4-8 mL, the dosage ratio of maleic anhydride and N, N-dimethylformamide in solution 1 is 0.05-0.1 mol: 40 mL, and the dosage ratio of melamine and N, N-dimethylformamide in solution 2 is 0.05-0.1 mol: 40 mL.

8. The anti-static ABS composite material based on carbon nanotubes according to claim 1, characterized in that: In step B3, the usage ratio of the functional monomer, maleic anhydride graft, cyclohexanone, benzoyl peroxide, petroleum ether and acetone is 5-8 g: 3-6 g: 30 mL: 0.4-0.6 g: 50 mL: 50 mL.

9. The anti-static ABS composite material based on carbon nanotubes according to claim 1, characterized in that: The lubricant is one of calcium stearate, polyethylene wax or zinc stearate, and the antioxidant is one of antioxidant 1010, antioxidant 1098 and antioxidant 1076.

10. A method for preparing the anti-static ABS composite material based on carbon nanotubes according to any one of claims 1 to 9, characterized in that: The following steps are involved: The raw materials are weighed by weight, and ABS resin, polycarbonate resin, composite conductive filler, lubricant, modified heat-resistant agent and antioxidant are mixed and stirred evenly, and then put into a twin-screw extruder, and melted, extruded and granulated to obtain an anti-static ABS composite material based on carbon nanotubes.

Citation Information

Patent Citations

  • Heat conduction and insulation plastic containing carbon nanotube filling material of special structure and preparation method thereof

    CN103554900A

  • Commercial antistatic and anti-wear polypropylene composite material and preparation method thereof

    CN107383598A

  • High-performance vinyl PTC (Positive Temperature Coefficient) composite material and preparation process thereof

    CN118772511A

  • Plastic material for Bluetooth headset shell and preparation method of plastic material

    CN119119702A

  • Development of metal molybdate carbon nanotube composite for suppression of electromagnetic pollution

    IN201811012614A

Cited By

  • A graphene antistatic PC composite material and preparation method thereof

    CN119752147A

  • A graphene antistatic PC composite material and preparation method thereof

    CN119752147B